Transforming Cultural Heritage into Sustainable Educational Tourism: The Case of Wahanarata Museum Yogyakarta - Nining Yuniati; Cello Joenathan Hutauruk; Yohana Agnescia (International Journal of Science and Environment (IJSE), 2026)
Wahanarata Museum Yogyakarta is a cultural heritage destination that preserves the royal carriage collections of the Yogyakarta Sultanate while simultaneously adapting to the contemporary tourism landscape through digital innovation and educational tourism development. This study aims to analyse the sustainability aspects of Wahanarata Museum from the perspectives of cultural preservation, social sustainability, and tourism development. The research employed a descriptive qualitative approach using data triangulation techniques through observation, interviews, and documentation to obtain a comprehensive understanding of the museum’s management and visitor experience. The findings reveal that the museum has implemented several sustainability-oriented strategies, including the revitalisation of museum facilities, the integration of digital technologies such as augmented reality and interactive educational media, and the involvement of Abdi Dalem as custodians of traditional values and cultural interpretation. These efforts demonstrate the museum’s attempt to balance heritage conservation with modern tourism demands. However, several challenges remain, particularly regarding limited bilingual interpretative information, insufficient digital promotion, and the need for more engaging educational communication strategies. From a socio-cultural perspective, the museum functions not only as a repository of historical artefacts but also as a living cultural space that maintains the continuity of Javanese traditions, collective memory, and local identity. The study concludes that the sustainability of cultural tourism destinations is not solely dependent on technological innovation or physical conservation, but also on the continuity of social values, community participation, and meaningful visitor experiences. Therefore, Wahanarata Museum has significant potential to become a model of sustainable cultural and educational tourism management that integrates heritage preservation, social sustainability, and digital transformation within the broader context of contemporary tourism development.